Human and machine creativity: social and ethical aspects of the development of artificial intelligence - Suchacka, Małgorzata; Muster, Rafał; Wojewoda, Mariusz (Creativity Studies, 2021)
The paper has a review character, and the presented analysis is based on theoretical considerations referring to the works of other authors. The aim of the paper is to draw attention to the importance of human creativity in the context of technology development, with special emphasis on artificial intelligence. For the purpose of exploration, the study applies philosophical methods, especially methods typical of ethical reflections, also supported by the analysis of existing data derived from social sciences, especially contemporary sociology. The study is synthetic in nature and includes theoretical considerations concerning several issues. Positive and creative possibilities of using artificial intelligence in social and economic life were shown. Potential threats that may be associated with the inappropriate use of artificial intelligence – robots and information systems were also identified. Potential threats resulting from too much trust of people in algorithms were shown. Attention is focused on social and ethical aspects of the human-machine relationship, with special emphasis on the dimension of pragmatism, trust and fascination with new technologies, as well as the principles of robot ethics. A significant part of the considerations also refers to the effects of automation processes, including the functioning of the labour market, human creative abilities and appropriate competences. The third part of the study indicates still undeveloped research fields related to artificial intelligence. The conducted analysis may indicate the direction for further sociological and philosophical research that considers the specificity of the artificial intelligence functioning and seeks support in interdisciplinary research teams.